Sudáfrica a inicios del siglo XX: la Posguerra Sudafricana - Varela, Hilda (El Colegio de México, 2009)
This article highlights the impact of Alfred Milner, British Governor of the Cape Colony and High Commissioner for Southern Africa, in the consolidation of South African racist thought during the immediate postwar epoch known as the “Milner period”. Although much has been written about the role played by Milner in the outbreak of the war, many authors tend to overlook his role in the formation of modern racist thought and segregation, and his attempts to turn South Africa into both a bastion of capitalism and “the white man's country” based on the hegemonic alliance between Afrikaners and British people. It is suggested that although the so called “Milner period” was very brief —from 1901 until his departure from South Africa in 1905— its impact on the modernization of racist exploitation was decisive in the future of South Africa in the coming decades.